2017
DOI: 10.1021/acsmedchemlett.7b00228
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antibacterial Activity of a Multivalent Polycationic Calix[4]arene–NO Photodonor Conjugate

Abstract: The role of nitric oxide (NO) as an antimicrobial and anticancer agent continues to stimulate the search of compounds generating NO in a controlled fashion. Photochemical generators of NO are particularly appealing due to the accurate spatiotemporal control that light-triggering offers. This contribution reports a novel molecular construct in which multiple units of 3-(trifluoromethyl)-4-nitrobenzenamine NO photodonor are clustered and spatially organized by covalent linkage to a calix[4]arene scaffold bearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…We have also compared the NO release rates and conditions with related NO donors. [31][32][33] We found that the current vesicle- (Fig. S9 †) to the existing NO releasing compounds, with an advantage of water solubility and bio-compatibility.…”
Section: Resultsmentioning
confidence: 78%
“…We have also compared the NO release rates and conditions with related NO donors. [31][32][33] We found that the current vesicle- (Fig. S9 †) to the existing NO releasing compounds, with an advantage of water solubility and bio-compatibility.…”
Section: Resultsmentioning
confidence: 78%
“…[77] Likewise, the use of antibacterial functional groups with NO may improve the action of either the functional group or NO, or both. [37c, 76c, 76d, 78] Gehring et al reported on mesoporous silica nanoparticles consisting of Rose Bengals (RB) and S -nitrosothiols that were capable of releasing both reactive oxygen species (ROS) and nitrogen species (i.e., NO) upon exposure to sunlight. [78a] The combination of ROS and NO is known to produce peroxynitrite anion (ONOO − ), a strong oxidant implicated in lipid peroxidation.…”
Section: Antibacterial Applicationsmentioning
confidence: 99%
“…Similarly, the Sortino group reported a polystyrene nanofiber comprised of NO photodonors and singlet oxygen O 2 ( 1 Δ g ) photosensitizers. [78b] Upon irradiation by visible light, the nanofiber was capable of simultaneously releasing NO and O 2 ( 1 Δ g ), with long (~100 μm) and short (10–100 nm) radii of antibacterial action, respectively. The combination of NO and O 2 ( 1 Δ g ) significantly improved the antibacterial action of the nanofiber against E. coli compared to the nanofiber releasing O 2 ( 1 Δ g ) alone.…”
Section: Antibacterial Applicationsmentioning
confidence: 99%
“…Calix[4]arenes are conformationally mobile molecules that have four conformers, that is, 1,3‐alternate, 1,2‐alternate, cone, and partial cone, with different cavity sizes. Therefore, calix[4]arenes have many potential applications in supramolecular host–guest chemistry and molecular sensing, such as the sensing of NO . Whilst calix[4]arene and its tetramethyl ether derivative are conformationally mobile at ambient temperature, the replacement of the methyl group with bulky propyl or larger groups inhibits interconversion between the conformers and allows their separation (Figure ) …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, calix [4]arenes have many potential applicationsi ns upramolecular host-guest chemistry and molecular sensing,s uch as the sensing of NO. [11,14,[27][28][29][30] Whilst calix [4]arene and its tetramethyl ether derivativea re conformationally mobile at ambient temperature, the replacement of the methyl group with bulky propylo rl argerg roups inhibits interconversion between the conformers and allows their separation ( Figure 1). [25,31] Previously,R athore, Kochi, and co-workersr eported the synthesis of as eries of calix [4]arene derivatives that displayed remarkably high association to NO + + ,w ith bindingc onstants greater than 2 10 8 m À1 .…”
Section: Introductionmentioning
confidence: 99%